ChemInform Abstract: Solution and Solid‐State Structural Chemistry of Actinide Hydrates and Their Hydrolysis and Condensation Products. Issue 13 (18th March 2013) - Knope, Karah E.; Soderholm, L.
Abstract Review: 328 refs.